High tibial osteotomy with external fixator in the varus gonarthritic knee - Maniscalco, P. (Acta Biomedica Atenei Parmensis, 2003)
High tibial osteotomy is a simple and safe method to correct the varus gonarthritic knee. Numerous follow-up studies have demonstrated that this procedure gives satisfactory functional results for 10-15 years after surgery, above all if a precise valgus hypercorrection of 8°-10° is carried out. The present study attempts to deal with another, less discussed topic: evaluation of the efficacy of external fixation after osteotomy synthesis with respect to the most common plate and screw synthesis as well as to the Insall procedure.